LEGAL PROTECTION FOR HEIRS IN CONTROL OF DIGITAL ASSETS IN THE FORM OF ELECTRONIC WALLET (E-WALLET) BALANCES - Lumban Gaol, Parida; Wardhani, Novea Elysa; Istani; Evi (International Journal of Cultural and Social Science, 2026)
This research focuses on analyzing the status of e-wallet balances as part of inherited assets in the Indonesian inheritance law system amidst the rapid development of the digital economy. The main issues examined are the suitability of the concept of e-wallet balances with the construction of assets in civil law and the legal and technical obstacles faced by heirs in the process of acquiring them. This research uses a normative legal research method with a statutory, conceptual, and comparative legal approach. Data were obtained through a literature review of laws and regulations, expert doctrines, court decisions, and relevant legal literature, then analyzed qualitatively and systematically. The results show that conceptually and legally, e-wallet balances qualify as intangible assets with economic value and are under the legal control of the heir, thus deserving of their status as part of inherited assets. However, the lack of explicit regulations regarding the inheritance of digital assets, coupled with strict personal data protection regimes and account security systems, creates legal uncertainty and practical obstacles for heirs in accessing e-wallet balances. The implications of this research emphasize the need for updating and harmonizing inheritance law regulations with personal data protection laws and digital financial services regulations, in order to create a digital asset inheritance mechanism that provides legal certainty, protects heirs' rights, and is responsive to technological developments.